2019
DOI: 10.1111/jns.12347
|View full text |Cite
|
Sign up to set email alerts
|

Liability of the voltage‐gated potassium channel KCNN3 repeat polymorphism to acute oxaliplatin‐induced peripheral neurotoxicity

Abstract: Thus far, there are conflicting results on the causal role of K+ channels in the pathogenesis of acute oxaliplatin‐induced peripheral neurotoxicity (OXAIPN). As such, we tested the hypothesis that the voltage‐gated K+ channel KCNN3 repeat polymorphism confers liability to acute OXAIPN. DNA from 151 oxaliplatin‐treated patients for colorectal cancer was extracted and genotyped. The incidence of acute OXIPN was measured by the OXA‐neuropathy questionnaire, while the severity of acute OXAIPN was scored basing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We read with interest the paper by Argyriou et al, 1 in which authors attempted to reproduce the results of a previous study conducted at our Institution, 2 regarding a possible association between acute oxaliplatin-related neurotoxicity and a short CAG-repeats polymorphism of KCNN3 channel.…”
Section: Dear Editormentioning
confidence: 98%
See 1 more Smart Citation
“…We read with interest the paper by Argyriou et al, 1 in which authors attempted to reproduce the results of a previous study conducted at our Institution, 2 regarding a possible association between acute oxaliplatin-related neurotoxicity and a short CAG-repeats polymorphism of KCNN3 channel.…”
Section: Dear Editormentioning
confidence: 98%
“…Moreover, authors set a cut-off point of 19 CAG repeats to distinguish long alleles and short alleles, but only 6% of patients had a long allele. 1 What is the meaning of a statistical analysis in which most patients (94%) were grouped together and compared to the remaining 6%? May be it could make sense (but we have lot of doubts on statistical power) if you suspect a higher incidence of neurotoxicity in those patients (6%) carrying a longer allele.…”
Section: Dear Editormentioning
confidence: 99%
“…There is no gold standard clinical assessment for CIPN or specifically for acute OXAIPN. In our study, 1 This approach may also be problematic due to the extremely high incidence of patients who demonstrate neurophysiological abnormalities following oxaliplatin treatment, leading to ceiling effects.…”
mentioning
confidence: 89%
“…The main message of the Modoni and Basso letter is that their previously published study, which showed a positive association between KCNN3 CAG repeat polymorphisms and increased risk of acute OXAIPN 2 is not comparable to our study, which failed to reproduce these results. 1 Identification of robust genetic risk factors that influence susceptibility to OXAIPN is critical in order to identify patients at risk prior to chemotherapy administration and enable tailored treatment approaches to minimize toxicity. To date, there have been difficulties in identifying genetic variants consistently associated with neurotoxicity risk across different patient cohorts.…”
mentioning
confidence: 99%
See 1 more Smart Citation